PTPN11 Gain-of-Function Mutations Affect the Developing Human Brain, Memory, and Attention. (27th July 2018) - Johnson, Emily M; Ishak, Alexandra D; Naylor, Paige E; Stevenson, David A; Reiss, Allan L; Green, Tamar
Abstract: The Ras-MAPK pathway has an established role in neural development and synaptic signaling. Mutations in this pathway are associated with a collection of neurodevelopmental syndromes, Rasopathies; among these, Noonan syndrome (NS) is the most common (1:2000). Prior research has focused on identifying genetic mutations and cellular mechanisms of the disorder, however, effects of NS on the human brain remain unknown. Here, imaging and cognitive data were collected from 12 children with PTPN11 -related NS, ages 4.0–11.0 years (8.98 ± 2.33) and 12 age- and sex-matched typically developing controls (8.79 ± 2.17). We observe reduced gray matter volume in bilateral corpus striatum (Cohen's d = −1.0:−1.3), reduced surface area in temporal regions ( d = −1.8:−2.2), increased cortical thickness in frontal regions ( d = 1.2–1.3), and reduced cortical thickness in limbic regions ( d = −1.6), including limbic structures integral to the circuitry of the hippocampus. Further, we find high levels of inattention, hyperactivity, and memory deficits in children with NS. Taken together, these results identify effects of NS on specific brain regions associated with ADHD and learning in children. While our research lays the groundwork for elucidating the neural and behavioral mechanisms of NS, it also adds an essential tier to understanding the Ras-MAPK pathway's role in human brain development.